TEKNOPOLITIK PEMIMPIN FEDERASI SEPAKBOLA INDONESIA DALAM IMPLEMENTASI TEKNOLOGI VIDEO ASSISTANT REFEREE - Andika Sanjaya; Mulia Ramdhan Fauzani; Slamet Riyadi; Agustia Landra Nugraha (Jurnal Komunikasi dan Kajian Media, 2024)
The Indonesian Football Federation or PSSI has been trying to implement video assistant referee (VAR) since the technology was introduced in 2018. The technology has the potential to improve the quality of referee decisions and produce fair matches. There are several obstacles that make PSSI have to postpone the implementation of VAR until 2024. This research aims to explain the chronology of PSSI facing various obstacles to implementing VAR technology. The research findings show the role of PSSI Chairman Erick Thohir as the holder of the political determinism aspect of technology. Technological determinism is not the main driver of change in society.